Positioning and development of Deszk in the Szeged Agglomeration - Balogh, Béla Ferenc; Koncz, Gábor (Studia Mundi – Economica, 2017)
According to information found in literature, those villages are able to develop which have a characteristic function, belong to a developing, diversified urban area and can be conveniently accessed. The typical rural problems are less common in rural villages near major cities, but the directions of development are often limited. At the beginning of our research we asked the following questions: Will Deszk become a self-developing village or will it remain being the suburb of Szeged? What kind of processes of suburbanization have taken place in the Deszk- Szeged region? During our primary research, we personally interviewed 165 people in the settlement. After the processing of the questionnaire with 13 questions we analyzed the results in table and text form.